Heat integration of a multi-product batch process by means of direct and indirect heat recovery using thermal energy storage. (25th February 2020) - Zuberi, M. Jibran S.; Olsen, Don; Liem, Peter; Wellig, Beat; Patel, Martin K.
Highlights: A case study is presented on heat integration of a multi-product batch process. The processes are optimized for direct & indirect heat recovery using heat storage. The heat recovery potential is estimated at 21–43% of the company's heat demand. The proposed heat exchanger & storage network designs were found to be economical. Abstract: Process heat integration in batch processes is a complex problem given their time dependent behavior and need for thermal energy storage. In case of multi-product batch processes the complexity increases further. Due to its intricacy, the topic has so far been hardly addressed in literature. This article presents a practical case study on heat integration of such complex batch processes in a medium-sized European textile plant using pinch analysis. The maximum heat recovery potential during different time slices of a day is estimated at 21–43% of the heat demand of the company. The processes are first optimized for direct heat recovery and a heat exchanger network is recommended with a maximum recovery potential of 85 GJ per day. The residual process requirements are then analyzed for indirect heat recovery by means of thermal energy storage. A closed intermediate loop and heat storage system with four temperature levels is recommended with an additional recovery potential of 17 GJ per day. The proposed heat exchanger and storage designs are both found to be cost‐effective with payback times ranging from 1 to 5 years. In spite of being technically rather demanding, more attention should be paid to thermal energy storage in batch processes since they are likely to offer more attractive additional energy saving potentials in industry. The approach provides an effective way of identifying practical solutions for heat integration in complex multi-product batch processes.